Genetics and the synthetic evolution theory as the main factors of evolutionary biology - L. T. Коtliarenko (History of science and technology, 2015)
The article highlights the problem on contemporary factors of evolutionary biology - genetics and synthetic theory of evolution. Modern evolutionary theory sees its main task in prediction the possibilities of evolutionary transformations on the basis of deep cognition of the evolutionary processes’ mechanism and, in its turn on this basis to guide the evolutionary process. One of the the most promising areas of biological science - genetics and synthetic evolutionism play an increasing role in solving this problem.